Variability in multiple embryo formation and seedling development of mandarin orange (Citru reticulata Blanco) of the north-eastern Himalayan region of India - Das, A.=700 1 Mandal, B.; Sarkar, J.
(En, Fr, Es)
Ilus., 15 ref.
Keywords: CITRUS RETICULATA; VARIACION GENETICA; EMBRIONES VEGETALES; POLIEMBRIONIA; SEMILLA; INDIA